Perancangan Sistem Informasi Kependudukan Menggunakan Metode Waterfall Pada Desa Jatibaru Berbasis Web - Ivan Reynata; M. Syaibani Anwar; Edora Edora (DPPM Universitas Pelita Bangsa, 2022)
In daily operational activities, the Jatibaru Village government performs several ways of archiving files, namely by conventional archiving for document files and using Microsoft Word for making correspondence. Meanwhile, the process of managing these files is done by manual writing on the agenda book, both physical document files and files in the form of files. In addition, if the village archive officer is not present, the letter request process is disrupted because the archive data is on a computer that can only be opened by the archive officer. This study uses the waterfall method to design a population data information system and request letters to web-based villages using PHP and MySQL. With the development of this system, the village office can record data on its villagers, especially Jatibaru Village, so that with accurate citizen data in the database it can be used for further information system development. Requests for letters to villages such as Certificates of Incapacity, Domicile Letters, Birth Certificates and others can be requested online by residents who have been registered at the village office, thereby speeding up the service process and facilitating the performance of village archive officers in serving the community, especially requests for letters from Village residents. Jatibaru, so that services at the Village Office can be maximized and fast. Keywords: Population data, Documents, Mail request system, Waterfall, PHP Mysql